REDISEÑO DE LOS PROCESOS DEL ÁREA DE COMPRAS E INVENTARIOS DE LA EMPRESA CONOS DEL SUR A TRAVÉS DE LA APLICACIÓN DEL BPM - DIANA CAROLINA MARTÍNEZ MONTERO; ÉVER ÁNGEL FUENTES ROJAS (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2018)
Currently it is common to find in organizations problems in terms of processes, technological infrastructure implementedand functional deficiencies, which leads to problems such as the lack of integration between areas, instability in theorganizational structure and the generation of value, both in productivity and in information systems; being reflected inlow performance and non-compliance with corporate policies. Conos del Sur SAS is a company with 10 years in thegastronomic market of the city of Bogotá, and has been affected by this problem, due to this and looking for a solutionto it the present article was developed. Based on the diagnosis made, in the area of purchases and inventories, opportunities for improvement were foundthrough the BPM[3], which allows focusing on the organizational structure, processes and systems that currently work inthe company, thus prioritizing, identify and classify essential processes in the company’s value chain. A knowledge baseis generated to establish activities and elements that must be continually evaluated and analyzed under BPM standards until the creation and registration of management indicators, leading to the generation of certain recommendations. Finally, the proposed solutions are applied, with very positive results such as the reduction of up to 58% in some costs,in which work can continue to achieve better results.